Process steam systems : - Merritt, Carey (John Wiley & Sons Inc., 2016)
The book is written with a system approach and looks at each part of the steam system individually with many examples of how to size and select the right equipment for a variety of applications. In addition to engineering principles, the text discusses good operations, maintenance, troubleshooting and commissioning practices of the entire steam system. Process Steam Systems provides a text for learning and a reference guide for operators, maintainers and engineers.